PERTUNJUKAN TARI CAMPUR BAWUR DALAM TRADISI SYAWALAN DESA LENCOH SELA BOYOLALI (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
Campur bawur dance is one of the folk art that has been born, alive and developing in the society of Cangkol Atas and has been acclaimed to be Lencoh’s. The performance of Campur Bawur dance is a media to express feeling and thoughts of the artist and involvement of the supportive society. The performance of Campur Bawur dance in Lencoh is one of the completion of the syawalan tradition dan village cleaning ceremony. The dance performance is the embodiment of validation or the belief of the Lencoh society in the existance of the power of the spirit of the dead. The spirits as the ancestor of the society, is considered to be able to protect and provide safety for the society. Syawalan tradition is a system of belief of the upcoming hapiness after one month fully fasting. Syawalan tradition is a media to strenghten the bond of friendship. Campur Bawur dance has simple motions and dinamic illustration. In every performance it is illustrated with the blend of Javanese gamelan in slendro harmony, added by other isntruments, suc as: drum, keyboard, adn cymbal. The research on campur Bawur is conducted with textual and contextual aproach. The textual research is to reveal Campur Bawur dance performance as a cultural product. The contextual research is conducted to reveal the background of why the Campur Bawur performance is held, the bevaviour pattern of the supportive society, and to analyze the cause of why the society hold such performance for the entertainment sake. The performance of Campur Bawur dance strengthen special characteristi of syawalan tradition. Kata kunci: campur bawur, tradisi, tari rakyat